Knowledge and attitudes about interactive digital tools for learning medical terminology among students - Banafi, Norah; Kaliyaperumal, Raji (Edelweiss Applied Science and Technology, 2024)
Learning is a self-contained process, and the most active components are the learners’ imaginative thinking and constructive cognitive engagement. It’s been established time and time again that effective interactions and communication between professors and students are crucial to learning. This essay aims to demonstrate the usefulness of interactive technology. This study used a descriptive study approach. Convenience sampling was used to pick 136 students from the College of Applied Medical Sciences at King Khalid University (KKU), Saudi Arabia, who enrolled in a 4-year Baccalaureate nursing program. This research was conducted in the 2021–2022 academic year. A questionnaire, such as the five-point Likert scale, was used to collect the data. SPSS was used to do statistical analysis on the collected replies. The findings showed that employing an interactive digital tool significantly improved the students’ understanding, and they also showed a good attitude regarding using the session to learn about medical terms.